W poszukiwaniu „narodowości w fotografice” - Szymanowicz, Maciej (Artium Quaestiones, 2018)
In Search for the “National Features in Photography” Summary The main point of the paper is the interest of Polish photographers in nationalist ideas, which has long been one of the forgotten and overlooked episodes in the history of twentieth-century Polish photography. The issue appeared for the first time in 1931-1933, when Polish photographic magazines published a debate about revealing national traits in a photo. It was an aftermath of the idea of the national style in Polish art, promoted since the early 1920s in relation to the needs of the state that just became independent. The greatest authorities of the time took part in the debate, including Jan Bułhak, Józef Świtkowski, Jan Sunderland, and Antoni Wieczorek, who were the main theorists of the Polish photography in the early 20th century. Analyzing the problem, they reverted to various arguments, from purely formal ones, assuming a characteristic tendency of Polish artists to choose particular forms and types of composition (a view based on the theory of pictorialism), through thematic (referring to collective memory and the historical experience of Poles), sociological, and even legal (based on the ideas of Leon Petrażycki). The same arguments were often used later throughout the century. The paper presents the development and theoretical basis of the debate in the early 1930s, as well as later evolution of the concepts which, coined at that time, contributed to the theory of Polish photography in the 20th century.